Developments in single-drop microextraction - Xu, Li; Basheer, Chanbasha; Lee, Hian Kee (Journal of Chromatography A, 2007)
Single-drop microextraction (SDME) has become a very popular liquid-phase microextraction technique because it is inexpensive, easy to operate and nearly solvent-free. Essentially, SDME combines extraction (and conceivably, cleanup) and concentration in a minimum number of steps, and thereafter, direct extract introduction into an analytical system. In this review, in order to encourage further development of SDME, we focus on its recent developments in its various guises. Its applications when used in combination with different analytical techniques, such as gas chromatography, high-performance liquid chromatography, inductively-coupled plasma mass spectrometry, capillary electrophoresis, mass spectrometry and electrothermal atomic absorption spectrometry, are summarized. SDME does have some limitations, and these are also discussed as well. Finally, an outlook on the future of the technique is given.